ANALISIS PENINGKATAN KEDISIPLINAN KERJA PEGAWAI PADA DINAS PETERNAKAN KABUPATEN BIMA - Nur Aisyah; Muhammad Badar (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to determine all disciplinary levels of ASN work at the Animal Husbandry Service of Bima Regency. The type of research used in this research is descriptive, the data analysis technique used is by using the validity test, reliability test and the one-sample t-test formula. The sample used was 46 ASN people. The results of statistical calculations are obtained, the t-value is -34,372 where the value is greater than the t-table (-34,372> 1,679), so that the hypothesis falls in the rejected area so that the result is Ho is rejected and Ha is accepted, the alternative hypothesis (Ha) states that the Discipline of Employee Work at the Animal Husbandry Service in Bima Regency is greater than or equal to 70% of the expected criteria, which is acceptable, and Ho is rejected or the initial hypothesis which shows that the increase in discipline of employee work at the Bima Regency Animal Husbandry Service is less than 70% of the expected criteria. is not yet good unacceptable. In this research, it can be taken from, 1. Increasing Employee Discipline at the Animal Husbandry Service of Bima Regency, based on the results of this study, where there is discipline of attendance / fixed working hours which is quite good, although there are still ASNs who are late for about 10-20 minutes, Because it is greater than 70% of the expected standard, 2. Increased Discipline of Employees who are bigger than uniforms, completing work on time or obeying the regulations are in accordance with the provisions of the regulations that apply to ASN.Kata Kunci: Work Discipline, Level of Discipline, Human Resource Management